Direct Imaging of Apoptosis Process of Neural Stem Cells Exposed to Porous Silica Nanoparticles - Wang, Yanli; Tan, Shun; Wang, Jia; Wu, Qiuxia; Chen, Xinxin; Deng, Xiaoyong; Lu, Qiong; Wu, Minghong (Current Nanoscience, 2010)
The present study was designed to examine the uptake, localization, and the cytotoxic effects of well-dispersed fluorescent porous silica nanoparticles (FITC-SiO2 NPs) in mouse neural stem cells (C 17.2, NSCs). NSCs were exposed to various concentrations of FITC-SiO2 NPs for different times and then the uptake and toxicity were assessed. Apoptotic cells were observed and analyzed by confocal microscopy and flow cytometry. Results of confocal microscopy examination revealed that silica nanoparticles were taken up into the cells. Cell viability decreased significantly as a function of both nanoparticle dosage (12- 240 μg/ml) and exposure time (12 h, 24 h 72 h). FITC-SiO2 NPs show marked toxicity at high concentration (240 μg/mL) after co-incubation for 72 h. There were clear dose- and timedependent silica-induced cytotoxicity and genotoxicity within the range of experimental concentrations. Interestingly, we have caught the whole process of NSCs apoptosis induced by FITC-SiO2 NPs. The understanding of such a mechanism may provide a scientific basis for the possible application of porous silica in drug delivery and controlled release.
Keywords: Cytotoxicity